Peran Guru PAI dalam Meningkatkan Kualitas Ibadah Puasa Sunnah Siswa di SMK Muhammadiyah Delanggu - Buana, Muhammad Tajmudin Sangga; Hafidz, Hafidz Hafidz (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Abstract: This study aims to describe the roles, strategies, and supporting and inhibiting factors faced by Islamic Religious Education teachers in improving the quality of students' sunnah fasting worship at Muhammadiyah Delanggu Vocational School. This study uses a qualitative approach with descriptive methods using purposive sampling techniques. Data collection in this study was carried out through various methods, such as interviews, observation, analysis, and documentation. The results of this study indicate that 1) Islamic Religious Education teachers act as educators, motivators, role models, and as evaluators who assess and provide feedback on the implementation of student worship., 2) The strategies used by Islamic Religious Education teachers are integrating learning materials with the practice of sunnah fasting worship, organizing routine programs of sunnah fasting together at school, giving rewards or appreciation to consistent students, involving the Rohis organization in religious activities, and creating a religious school environment, 3) Factors that support the efforts of Islamic Religious Education teachers are motivation and full support from Islamic Religious Education teachers, parental involvement, a religious school environment, and the existence of the Rohis organization that helps implement the program. The factors that hinder this strategy are the influence of the environment outside the school which does not support the habit of worship, as well as the density of school activities in the form of practical assignments, extracurricular activities, and internships which make it difficult for students to be consistent in carrying out sunnah fasting.Abstrak: Penelitian ini bertujuan untuk mendeskripsika, peran, strategi, serta faktor pendukung dan penghambat yang dihadapi guru pai dalam meningkatkan kualitas ibadah puasa sunnah siswa di SMK Muhammadiyah Delanggu. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif dengan menggunakan teknik purposive sampling. Pengumpulan data dalam penelitian ini dilakukan melalui berbagai metode, seperti wawancara, observasi, analisis, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa 1) Guru PAI berperan sebagai edukator, motivator, teladan, serta sebagai evaluator yang menilai dan memberikan umpan balik atas pelaksanaan ibadah siswa., 2) Strategi yang digunakan guru PAI yakni mengintegrasikan materi pembelajaran dengan praktik ibadah puasa sunnah, menyelenggarakan program rutin puasa sunnah bersama di sekolah, memberikan reward atau apresiasi kepada siswa yang konsisten, melibatkan organisasi Rohis dalam kegiatan keagamaan, serta menciptakan lingkungan sekolah yang religius, 3) Faktor-faktor yang mendukung upaya guru PAI yakni motivasi dan dukungan penuh dari guru PAI, keterlibatan orang tua, lingkungan sekolah yang religius, serta keberadaan organisasi Rohis yang membantu pelaksanaan program. Adapun faktor yang menghambat strategi ini yakni pengaruh lingkungan luar sekolah yang kurang mendukung kebiasaan beribadah, serta padatnya kegiatan sekolah berupa tugas praktik, ekstrakurikuler, dan magang yang membuat siswa sulit beristiqamah dalam menjalankan puasa sunnah.